USG Liver examination of Tahfiz Quran Primary School students in Berastagi - Daulay, Elvita Rahmi; Z. Tala, Mohammad Rhiza (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
The Liver is the largest solid organ in the human body and has many roles in maintaining a healthy body. Non-alcoholic Fatty Liver Disease (NAFLD) is a fatty liver without being accompanied by the consumption of alcohol. NAFLD is a condition that is often found in children. The majority of patients with NAFLD are asymptomatic. The diagnosis of NAFLD is usually made through imaging the liver or abnormal liver function with the presence of metabolic syndrome and or overweight. Ultrasound has high sensitivity and specificity in diagnosing NAFLD into an imaging technique that is widely used in cases with fatty liver. This community service is done to find out about the liver health of Tahfiz Quran Primary School students in Berastagi. It is also an effort to screening and early detection of liver health problems in those students. It also aims to raise awareness of heart health among students, teachers, and parents. Ultrasound liver examination of the 59 Tahfiz Quran Primary School students. Educational activities also done to educate the students about liver health. Out of 59 students, 10 students (16.9%) had mild fatty liver, 1 student (1.7%) had a calcified liver, and 36 students (61.0%) had ascites. Fatty liver was found among the students also the majority of the students had ascites.